Preparation, Structural Study, Theoretical Treatment and Biological Activity of Cr (III), Ni (II), Cd (II) and V (IV) Complexes of Tetradentate Ligand Bis [4-Phenyl-3 (2- Propenyl) Thio-1, 2, 4-Triazole-5yl] Methane - Alias, Mahasin F; Hamza, Manal O; Kareem, Tamara A (Al-Nahrain Journal of Science, 2011)
Some transition metal complexes Cr (III), Ni (II), Cd (II) and V (IV) Complexes of olefinic bistriazole as a ligand have been synthesized and characterized. The prepared complexes were identified and their structural geometries were suggested by using Flame Atomic Absorption technique, FT-IR and Uv-Visible Spectrophotometer as well as to Magnetic Susceptibility and Conductivity measurement. Semi-empirical methods (PM3 and MINDO/3) were carried out to evaluate the vibration frequencies, heat of formation (∆Hºƒ) and binding energy (ΔEb) for all metal complexes. And it is also studying their biological activity against two selected microorganisms (pseudomonas aeruginosa and staphylococcus aureus).